Identifikasi Fitokimia Ekstrak Daun Magenta (Peristrophe Bivalvis (L.) Merr) serta Uji Toksisitas Akut pada Mencit Putih Jantan dengan Penentuan LD50 - Ketut Agus Adrianta (Jurnal Ilmiah Medicamento, 2021)
Magenta leaves (Peristrophe bivalvis (L.) Merr) are used as natural dyes for the food and pharmaceutical industries. Apart from acting as decorations in food ingredients, Magenta leaves have many biological activities in the pharmaceutical field including treatment of blood diseases, anti-hypertension, anti-hyperlipidemia, fungistatic and antibacterial properties. For the safety of the utilization of magenta leaves if used as a treatment, it is necessary to conduct research to determine the content of secondary metabolites and conduct acute toxicity tests of Magenta leaf extract in male white mice measured quantitatively with LD50. This type of research is experimental with a randomized post-test only control group design. Samples of 25 male white mice divided into 1 control group and 4 treatment groups, each consisting of 5 mice. The control group (P1) give a placebo, treatment group 2 (P2), 3 (P3), 4 (P4) and 5 (P5) were given a solution of Magenta leaf extract with successive doses with a dose of 1 g / KgBB, 2 g / KgBB, 4 g / KgBB and 8 g / KgBB. The test preparation was given orally with only one administration at the beginning of the study period. Extraction was carried out using 80% ethanol by maceration. Testing the content of secondary metabolites in Magenta leaf extract was carried out by tube reaction. After identification of secondary metabolites, the extract of the positive Magenta plant contains alkaloid compounds, flavonoids, saponins, triterpenoids, and tannins. The LD50 value of Magenta leaf extract is greater than 8 g / kgBB. Magenta leaf extract is a material that is practically non-toxic based on Loomis criteria (1978) and no significant clinical symptoms of acute toxicity were found in all experimental animals.